Facilitation of non-indigenous ascidian by marine eco-engineering interventions at an urban site. Issue 1 (2nd January 2023) - Schaefer, Nina; Sedano, Francisco; Bishop, Melanie J.; Dunn, Kate; Haeusler, M. Hank; Yu, K. Daniel; Zavoleas, Yannis; Dafforn, Katherine A.
Abstract: Marine artificial structures often support lower native species diversity and more non-indigenous species (NIS), but adding complex habitat and using bioreceptive materials have the potential to mitigate these impacts. Here, the interacting effects of structural complexity (flat, complex with pits) and concrete mixture (standard, or with oyster shell or vermiculite aggregate) on recruitment were assessed at two intertidal levels at an urban site. Complex tiles had less green algal cover, oyster shell mixtures had less brown ( Ralfsia sp. ) algal cover. At a low tidal elevation, the non-indigenous ascidian Styela plicata dominated complex tiles. Additionally, mixtures with oyster shell supported higher total cover of sessile species, and a higher cover of S. plicata. There were no effects of complexity or mixture on biofilm communities and native and NIS richness. Overall, these results suggest that habitat complexity and some bioreceptive materials may facilitate colonisation by a dominant invertebrate invader on artificial structures.